1973
DOI: 10.1063/1.1680556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of excluded volume on the dipole moments of chain molecules

Abstract: Dielectric constants have been determined for dimethylsiloxane chains (CH3)3Si[OSi(CHJ210Si(CH3)3 in the thermodynamically good solvent cyclohexane and in the undiluted state, for degrees of polymerization x + 1 ranging from lQ2 to 1/nm 2 (where <,...2> is the mean-square dipole moment of a chain consisting of n = 2x + 2 bond dipoles of magnitude m) is independent of chain length, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

1975
1975
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 47 publications
2
8
0
1
Order By: Relevance
“…For the reasons outlined above, the comparison between theoretical and experimental results requires a close ex- In a recent work, Cais and Brown18 examined the stereoconfiguration of PVB by NMR and found that racemic placement becomes more likely with decreasing polymerization temperature, just as in PVC. For samples obtained at 30 °C, the probability of meso dyads is 46%, which is in very good agreement with our results. The value of 0.53 found for the dipole moment ratio of PVB chains in dioxane is in good agreement with the value 0.57-0.52 obtained by the RIS model assuming that ß = 0 and Pi = 0.4-0.5.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For the reasons outlined above, the comparison between theoretical and experimental results requires a close ex- In a recent work, Cais and Brown18 examined the stereoconfiguration of PVB by NMR and found that racemic placement becomes more likely with decreasing polymerization temperature, just as in PVC. For samples obtained at 30 °C, the probability of meso dyads is 46%, which is in very good agreement with our results. The value of 0.53 found for the dipole moment ratio of PVB chains in dioxane is in good agreement with the value 0.57-0.52 obtained by the RIS model assuming that ß = 0 and Pi = 0.4-0.5.…”
Section: Discussionsupporting
confidence: 92%
“…Dielectric measurements were carried out on solutions of sample A in dioxane at 60 °C. Similar measurements were made on solutions of sample B in dioxane at 30 °C. In another series of experiments at 30, 40, 50, and 60 °C dielectric measurements were made on solutions of sample A in 1-methylnaphthalene.…”
Section: Resultssupporting
confidence: 58%
“…Their analysis proceeds through the use of the theoretical elastic equation of state for networks of Gaussian where r is the number of chains per unit volume, k is the Boltzmann constant, (r2)¡ is the mean-square end-to-end distance of a network chain in the undistorted state but at the same volume as the distorted network, and (r2>0 is the already defined unperturbed dimensions. On this basis3'26 '33,34 d In <r2)0/dT = -[a In (f/T)/dT]p,Lß/( 2 -1) (9) The stress-strain isotherms, thus analyzed, yield d In <r2)0/dT = 0.27, 0.52, and 0.51 X "3 K-1 for a = 1.2, 1.4, and 1.6, respectively. The resulting average value is d In <r2)0/dT = 0.43 ± 0.11 X 10~3 K-1.…”
Section: Resultsmentioning
confidence: 99%
“…This difference is due to the difference in chain stiffness and local chain conformation which arises from that in stereochemical composition ( f r ) . The PDMS chain has also been found to be of rather strong helical nature, although not so strong as the a-PMMA chain, from an analysis of the data for its mean-square electric dipole moment 〈μ 2 〉, which shows that the ratio 〈μ 2 〉/ x as a function of the degree of polymerization x exhibits a maximum. , Since the a- and i-PMMA chains as well as the PDMS chain have type-B dipoles perpendicular to the chain contour, it is interesting to investigate the dependence on x of 〈μ 2 〉/ x of PMMAs. This is the purpose of the present paper.…”
Section: Introductionmentioning
confidence: 99%